The Influence of Cash Turnover Rate, Credit Turnover Rate, and Capital Adequacy on Profitability in Savings and Loan Cooperatives in Denpasar - Jyotika Artha Sadiwi, Ni Putu; Rismayanti, Kadek Intan; Putu Ratih, Ida Ayu; Padmaningrum, Ni Made; Jantina, Ni Wayan; Gama, Agus Wahyudi Salasa; Astiti, Ni Putu Yeni (AIBPM Publisher, 2024)
Profitability is a company's ability to gain profits in a certain period. This research aims to test and provide empirical evidence of the influence of cash turnover rate, credit turnover rate, and capital adequacy on the profitability of savings and loan cooperatives in the East Denpasar district. The population in this study was 32 cooperatives in the East Denpasar District area. The sampling technique used in this research was purposive sampling. Based on the criteria considered in sampling, a sample of 32 cooperatives in East Denpasar District was obtained, with three years of observation so that the number of observations was 96. The data collection method in this research was by using non-participant observation methods. The data analysis technique used is multiple linear regression analysis. The results of the study show that cash turnover has a positive and significant effect on the profitability of savings and loan cooperatives in the East Denpasar sub-district. Credit turnover has a positive and significant effect on the profitability of savings and loan cooperatives in the East Denpasar sub-district. Capital adequacy has a negative and significant effect on the profitability of savings and loan cooperatives in East Denpasar sub-district